Two‐sided heterogeneity: New implications for input trade - Ara, Tomohiro (Review of international economics, 2023)
This article develops a heterogeneous firm model to analyze selection effects at different production stages on trade‐induced intra‐industry resource reallocations. Using a two‐country symmetric setting in which both inputs and final goods are costly to trade subject to selection, we show that the trade elasticity of intermediate goods is endogenously greater than that of final goods due to an extra adjustment in the extensive margin. We also show that the welfare gains from input trade liberalization are greater than those from output trade liberalization if and only if the domestic input share is smaller than the domestic output share.